2015
DOI: 10.1007/s12041-015-0580-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of endangered Aquilaria malaccensis revealed potential for future conservation

Abstract: The endangered Aquilaria malaccensis,is an important plant with high economic values. Characterization of genetic diversity and population structure is receiving tremendous attention for effective conservation of genetic resources. Considering important repositories of biological diversity, the genetic relationships of 127 A. malaccensis accessions from 10 home gardens of three states of northeast India were assessed using amplified fragment length polymorphism (AFLP). Of the 1153 fragments amplified with four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In this study, the low F ST indicated weak genetic differentiation existing among R. trigyna populations. Such low genetic differentiation has been reported for other narrowly distributed endangered species, such as Aquilaria malaccensis , Thuja sutchuenensis , and T. mongolica (Cheng et al., 2020; Qin et al., 2021; Singh et al., 2015). AMOVA demonstrated that 98.24% of the overall genetic variation in R. trigyna populations occurred within populations (Table S3), confirming weak genetic differentiation among R. trigyna populations.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, the low F ST indicated weak genetic differentiation existing among R. trigyna populations. Such low genetic differentiation has been reported for other narrowly distributed endangered species, such as Aquilaria malaccensis , Thuja sutchuenensis , and T. mongolica (Cheng et al., 2020; Qin et al., 2021; Singh et al., 2015). AMOVA demonstrated that 98.24% of the overall genetic variation in R. trigyna populations occurred within populations (Table S3), confirming weak genetic differentiation among R. trigyna populations.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, high levels of genetic diversity can be maintained in some rare and endangered species at small population sizes (Rossetto et al 1995;Ci et al 2008;Gordon et al 2012;Zhao et al 2012). Wu et al (2015) have also reported high genetic Leimu et al 2006) and also to the earlier reports in other endangered tree species such as Metrosideros boninensis (Kaneko et al 2008), Ostrya rehderiana (Li et al 2012), Aquilaria malaccensis (Singh et al 2015), Pulsatilla patens (Szczecinska et al 2016). Analysis of molecular variance (AMOVA) showed that 27% of genetic variation occurred between the 10 populations, whereas 73% of genetic variation occurred within these populations indicating weak differentiation between the sampled populations.…”
Section: Discussionmentioning
confidence: 84%
“…ISSR marker system employed in the present investigation has exhibited high PIC value that indicates its suitability and informativeness (Botstein et al 1980). The adequacy of polymorphism detected by a marker system is essential for estimation of population genetic parameters, for this, it should sample optimum polymorphic loci representing the entire genome (Staub et al 2000;Mariette et al 2002;Luikart et al 2003;Singh et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among contributors for the papers on alternative medicine, Wagh et al 2017 On the other hand, there is 1 paper out of the total 19 papers, demonstrates concern to the ailing environmental condition relating to the species Aquilaria malaccensis . The paper which is attained by Indian scholars delves in genetics in an attempt to provide a potential solution as a future conservation for the endangered species (Singh et al, 2015).…”
Section: Trend Of Research On Aquilaria Malaccensis 2015-2019 Based Omentioning
confidence: 99%